1975
DOI: 10.3109/10826087509026707
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics in Heroin Addicts and Nonaddicted Prisoners Using the Edwards Personality Preference Schedule

Abstract: The present study compares the self-reported personality characteristics of heroin addict and nonaddict prisoners using the Edwards Personality Preference Schedule (EPPS) which was corrected for social desirability. Seventy pairs of addicted and nonaddicted criminal offenders were matched for age, education, intelligence, and home environment. The addicted offenders were identified by the pattern of their response to the EPPS as reflected by the significant multivariate results. In addition, significant univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Rating patterns across groups showed prominent elevations on Number of Unfavorable Adjectives Checked, Aggression, and Succorance. The results are consistent with reports by Reith, Crockett, and Craig (1975), which point to a constellation of features among addict self-descriptions including exaggerated dependency needs, difficulties in appropriate expression of hostility, excessive demands for interpersonal support and attention, and limitations in responding in kind. Mutual exaggeration of such features provides an important target for therapeutic intervention and assessment of program impact.…”
Section: Discussionsupporting
confidence: 90%
“…Rating patterns across groups showed prominent elevations on Number of Unfavorable Adjectives Checked, Aggression, and Succorance. The results are consistent with reports by Reith, Crockett, and Craig (1975), which point to a constellation of features among addict self-descriptions including exaggerated dependency needs, difficulties in appropriate expression of hostility, excessive demands for interpersonal support and attention, and limitations in responding in kind. Mutual exaggeration of such features provides an important target for therapeutic intervention and assessment of program impact.…”
Section: Discussionsupporting
confidence: 90%
“…Although Task 3 did not properly operationalize the aggression condition, the results of• the rate of responding provide data that contradict a contention that addicts •lack endurance and persistence (Reith, Crockett, & Craig 1975;Sheppard et al 1975). For the male addicts and, to a lesser extent, for faTale addicts, responding was equal to that of nonaddict delinquents and nonaddict non delinquents during the reinforcenent periods and was higher than either of the other groups during both extinction periods.…”
Section: Discussioomentioning
confidence: 82%
“…For another type, drug use may decrease a.lnPst constant feelings of anger and irritability. Reith, Crockett, and Craig (1975) found that addicts have both high aggressivity and a high need for succorance as measured by the Edwards Personal Preference Schedule. They note that these are contradictory needs ,involving a conflict that would be extremely difficult to resolve.…”
Section: Chaptermentioning
confidence: 99%